Evaluation of urban energy transition and identification of barrier factors under the “dual carbon” goals: an empirical study of the Yangtze River economic belt - Yan, Haoran; Gao, Jingke; Li, Shixiang; Bai, Jun; Liu, Ziyuan; Mai, Chen (Frontiers in Environmental Science, 2025)
The Yangtze River Economic Belt is a critical strategic region for China’s economic development. Accurately assessing the energy transition level of the Yangtze River Economic Belt and identifying key barriers in the region are essential for achieving China’s carbon neutrality goals. Currently, technical assessments of urban-scale energy transitions are limited, with insufficient consideration of the comprehensive contributions of supporting transformations to the broader energy transition. This study develops a comprehensive evaluation framework for urban energy transition based on six dimensions: environmental pollution, energy consumption, environmental governance, resource endowment, technological innovation, and policy guidance. Through the integrated index model and barrier degree model, a quantitative analysis is conducted to explore the dynamics and potential mechanisms of energy transition in the Yangtze River Economic Belt. The results show: (1) The overall level of urban energy transition increased by 35.86%, with persistent inter-city disparities, though their intensity has been alleviated. Over time, spatial differentiation has gradually weakened, transitioning from a core-periphery pattern to a more balanced distribution. (2) The sample cities were categorized based on four criteria: geographical region, urban size, energy transition level, and the developmental stages of resource-based cities. Under each of these four criteria, the city types with the highest energy transition performance were identified as eastern cities, large cities, high-level energy transition cities, and regenerated cities. (3) Within the entire sample, the contributions of environmental governance, resource endowment, and policy guidance to the resistance of the transition are 20.64%, 18.75%, and 18.34%, respectively. The obstacle degree value for environmental pollution is the lowest, indicating that progress in this area could further support urban energy transition efforts. This study establishes an analytical framework for evaluating urban-scale energy transitions and provides the first systematic assessment of energy transition in the Yangtze River Economic Belt, offering valuable insights applicable to other regions of China and countries or regions with similar socio-economic and developmental contexts.